2017
DOI: 10.2298/bah1704397c
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameters, carcass and meat quality of slaughter pigs with and without liver milk spots

Abstract: The aim of this study was to determine the influence of liver milk spots on hematological, carcass and meat quality parameters in slaughter pigs. A total of 120 pigs with a live weight of approximately 115 kg and six months old were examined. Any signs of liver milk spots were recorded as present or absent according to Welfare Quality® protocol (2009). A complete blood picture was investigated. The following carcass quality parameters were measured: live, hot and cold carcass weights, dressing percentage, back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although the study population in the current research involved 3066 pigs from 102 different batches representative for the same number of herds and farms, the authors are aware of two major limitations of this study. The first limitation is a lack of knowledge about herd health and management, since various factors have an influence on pork quality, such as genetic variables, feeding, slaughter weight, and sex, as well as preslaughter and slaughter conditions [ 23 , 32 , 34 , 39 , 52 , 53 , 56 , 57 , 58 ]. The second limitation is a restricted analysis of meat characteristics focusing only on basic quality parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the study population in the current research involved 3066 pigs from 102 different batches representative for the same number of herds and farms, the authors are aware of two major limitations of this study. The first limitation is a lack of knowledge about herd health and management, since various factors have an influence on pork quality, such as genetic variables, feeding, slaughter weight, and sex, as well as preslaughter and slaughter conditions [ 23 , 32 , 34 , 39 , 52 , 53 , 56 , 57 , 58 ]. The second limitation is a restricted analysis of meat characteristics focusing only on basic quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A Hanna HI 99163 portable pH meter (Hanna Instruments, Smithfield, Rhode Island, USA) was used to measure initial meat temperature (T I ) and pH (pH 45 ) 45 min postmortem on the musculus longissimus dorsi, pars lumbalis, on the left half of the carcass, at the level of the 10th and 11th ribs. Following Cobanovic et al (2017) [39], the carcasses showing pH 45 values lower than 6.0 were classified as PSE (pale, soft, exudative) meat, whereas those with pH45 values higher than 6.4 were classified as DFD (dark, firm, dry) meat. Carcasses with a pH 45 between 6.0 and 6.4 were classified as pork of normal quality [39].…”
Section: Carcass and Meat Quality Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH (pH 45min ) and temperature (T 45min ) of the M. longissimus dorsi were measured (in triplicate) 45 min postmortem on the left half of the carcass at the level of the 10th and 11th ribs using a pH‐meter Testo 205 (Testo AG). The pork quality classes were determined according to Čobanović et al () using pH 45min . The carcasses showing pH 45min values lower than 6.0 were classified as pale, soft, and exudative (PSE) meat, while the carcasses showing pH 45min values higher than 6.4 were classified as dark, firm, and dry (DFD) meat.…”
Section: Methodsmentioning
confidence: 99%
“…Abattoir‐detected pathologies cause significant negative effects such as: (a) farm financial losses attributed to decreased average daily weight gain, growth rate and feed digestibility, high morbidity and mortality, and increased medication and veterinary expenses (Jäger et al, ; Sanchez‐Vazquez et al, ); (b), abattoir operator losses due to trimming and discarding of organs unfit for human consumption (Jäger et al, ; Sanchez‐Vazquez et al, ); and (c) lower carcass quality (Čobanović et al, ; Permentier et al, ). Despite the fact that numerous studies have revealed that pork quality is affected by many different factors, only a few papers have been published about the relationships between pneumonia, pleurisy (Dailidavičienė, Januškevičienė, Jukna, Pockevičius, & Kerzienė, ; Dailidavičienė, Januškevičienė, Zaborskienė, & Garmienė, ; Karabasil et al, ; Minkus, Schutte, von Mickwitz, & Beutling, ; Permentier et al, ), liver milk spots (Čobanović et al, ; Theodoropoulos, Deligeorgis, Fegeros, Papavasiliou, & Rogdakis, ) and pork quality.…”
Section: Introductionmentioning
confidence: 99%